Reducing Deforestation and Trading Emissions: Economic Implications for the post-Kyoto Carbon Market - Jayant A. Sathaye; Niels Anger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper quantitatively assesses the economic implications of crediting carbon abatement from reduced deforestation for the emissions market in 2020 by linking a numerical equilibrium model of the global carbon market with a dynamic partial equilibrium model of the forestry sector. We find that integrating avoided deforestation in international emissions trading considerably decreases the costs of post-Kyoto climate policy – even when accounting for conventional abatement options of developing countries under the CDM. At the same time, tropical rainforest regions receive substantial net revenues from exporting carbon-offset credits to the industrialized world. Moreover, reduced deforestation can increase environmental effectiveness by enabling industrialized countries to tighten their carbon constraints without increasing mitigation costs. Regarding uncertainties of this future carbon abatement option, we find both forestry transaction costs and deforestation baselines to play an important role for the post-Kyoto carbon market.
Keywords: Q23; C60; D61; Q58; 330; Climate Change; Kyoto Protocol; Emissions Trading; Deforestation; Klimaschutz; Abholzung; Aufforstung; Kosten-Nutzen-Analyse; Emissionshandel; Welt